PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR KOGNITIF IPAS KELAS V - Nisa, Rida Khoirin; Pramasdyahsari, Agnita Siska; Suharno, Suharno; Roshayanti, Fenny (Universitas Negeri Medan, 2024)
Abstract: The purpose of this research is to determine the improvement of IPAS cognitive learning outcomes in grade VA SDN Kalicari 01 by applying the Problem Based Learning model. The method used is Classroom Action Research which is carried out in two cycles. In the pre-cycle stage, the average score of students was 62.79 with a completion percentage of 35.71%. After applying the PBL model in cycle I, the average score increased to 74.46 with a learning completeness percentage of 71.43%. In the second cycle, the average score of students increased again to 82.71 with a percentage of learning completeness of 82.14%. This study concluded that the PBL model is effective in improving the IPAS cognitive learning outcomes in grade VA SDN Kalicari 01. Keyword: Cognitive Learning Outcomes, Problem Based Learning Model, IPAS Abstrak: Penelitian ini bertujuan guna mengetahui peningkatan hasilbelajar kognitif IPAS kelas VA SDN Kalicari 01dengan menerapkan model Problem Based Learning. Metode yang digunakan yaitu Penelitian Tindakan Kelas yang dilaksanakan dalam dua siklus. Pada tahap pra siklus, nilai rata-rata siswa adalah 62,79 dengan persentase ketuntasan sebesar 35,71%. Setelah diterapkan model PBL pada siklus I, nilai rata-rata meningkat menjadi 74,46 dengan persentase ketuntasan belajar sebesar 71,43%. Pada siklus II, nilai rata-rata siswa kembali meningkat menjadi 82,71 dengan persentase ketuntasan belajar sebesar 82,14%. Penelitian ini memberikan kesimpulan bahwa model PBL efektif untuk meningkatkan capaian belajar kognitif IPAS siswa kelas VA SDN Kalicari 01.Kata Kunci: Hasil Belajar Kognitif, Model Problem Based Learning, IPAS